Types of Balinese Script Block Structure using Symbol Block Analysis - Ida Bagus Mas Abdi Putra; I K. Paramarta I K. Paramarta (Bina Nusantara University, 2023)
The research aimed to examine the existence of Balinese script block structure types in the Balinese Latin script dictionary to make it easy and correct to read Balinese script. The Balinese language was encountering an urgent crisis in poor intergenerational speaker transmission, the emergence of the stigma of reading Balinese script was very difficult, and the actual use of Balinese script was increasingly narrow and limited. The research applied qualitative methods as a reference method in completing research. The research instrument used observation, documentation, and writing methods as data collection methods. The types of Balinese script block structures found in the Balinese Latin script dictionary of the 21 most used entries are (1) V-CV-CC, (2) V-CCV-CC, (3) CV-CV-CC, (4) CV-C, (5) V-CCV. The concept of the syllabogram block structure differs from the phonological syllables in the Balinese script writing system. The syllabogram shows block breaks, while the phonological syllables are based on loudness level. Understanding these differences makes it easier to read Balinese script, which is different from Latin script. The research proves the application of the concept of Balinese script block structure types to relevant Balinese script elements based on the concept of syllables as a reference for reading and writing Balinese script. The research provides a reference and guide in reading, writing, and transliterating Balinese script into Latin script with adequate concepts and theories.